Evolving southwest African response to abrupt deglacial North Atlantic climate change events - (:unkn) unknown (My University, 2015)
Climate change during the last deglaciation was strongly influenced by the 'bipolar seesaw', producing antiphase climate responses between the North and South Atlantic. However, mounting evidence demands refinements of this model, with the occurrence of abrupt events in southern low to mid latitudes occurring in-phase with North Atlantic climate. Improved constraints on the northesouth phasing and spatial extent of these events are therefore critical to understanding the mechanisms that propagate abrupt events within the climate system. We present a 19,400 year multi-proxy record of climate change obtained from a rock hyrax midden in southernmost Africa. Arid anomalies in phase with the Younger Dryas and 8.2 ka events are apparent, indicating a clear shift in the influence of the bipolar seesaw, which diminished as the Earth warmed, and was succeeded after ~14.6 ka by the emergence of a dominant interhemispheric atmospheric teleconnection.
Keywords: African Research